Neuro-immune interactions at single-cell resolution in neurodevelopmental, infectious, and neurodegenerative diseases - Hyun Jung Park; Hosung Jung (Animal Cells and Systems, 2022)
Recent technological advance in single-cell and single-nucleus transcriptomics has made it possible to generate an unprecedentedly detailed landscape of neuro-immune interactions in healthy and diseased brains. In this review, we overview the recent literature that catalogs single-cell-level gene expression in brains with signs of inflammation, focusing on maternal immune activation, viral infection, and auto-immune diseases. The literature also includes a series of papers that provide strong evidence for immunological contributions to neurodegenerative diseases, which, in a strict sense, are not considered neuroinflammatory. To help with the discussion, we present a diagram of experimental and analytical flows in the single-cell analysis of the brain. We also discuss the recurring themes of neuro-immune interactions and suggest future research directions.